Development of Optical Equipment Learning Media with the Utilization of Used Goods in Elementary School Science Subjects - Angga Eko Novanto; Sutama Sutama; Anatri Desstya; Yenny Prastiwi; Laili Etika Rahmawati (Postgraduate, University of Mataram, 2023)
The problem that often occurs in the science learning process is the lack of involvement of students in using learning media, this is due to the lack of learning media available in schools. This study aims to test the feasibility of optical instrument learning media products with the use of used goods in elementary school science subjects. This type of research uses the R&D (Research and Development) model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The subjects used were 9 grade IV students of SDN Sumberasri 04 Blitar. Data collection in the form of interview results, expert validation sheets, student response questionnaires, and observation sheets. Data analysis in the form of qualitative data analysis and quantitative data analysis. The questionnaire used is in the form of Likert scale. The results showed validation carried out by media experts on simple microscope products 91.66%, simple magnifying glasses 95.85%, and simple periscopes 95.85%, and the response of students obtained an average score of 3.55. The results stated that media products are classified as very suitable for use in elementary school science learning